Road construction - Khairul Zamil, Muhammad Umar Haziq (Universiti Teknologi MARA, Perak, 2019)
Roads make a crucial contribution to economic development and growth and bring important social benefits. They are vital importance in order to make a nation grow and develop. A better road can make the traffic smoother as it in a good condition and safe to be used. This report reviews for road construction method and identify the machineries used to construct the road. The road construction method used is flexible pavement and focusing on laying premix pavement. The road construction was done according to design of road plan provided. The road construction also following the specifications of road work. A road construction must comply with the principle of design such as recommended thickness of pavement and the material used. In sums, all the work was done successfully and properly according to the right specifications by Jabatan Kerja Raya (JKR).